Influence of Cr doping on optical and photoluminescent properties of CdTe - Ilashchuk, М.I.; Parfenyuk, O.A.; Ulyanytskiy, K.S.; Brus, V.V.; Vakhnyak, N.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Spectra of transmission and low-temperature photoluminescence of CdTe:Cr crystals have been investigated for concentrations of the doping impurity (Cr) from 1∙10¹⁷ to 4∙10¹⁹ cm⁻³ in the melt. We have found additional absorption bands with maxima at λ₁ = 1.9 μm and λ2 = 7.0 μm induced by the presence of this dopant. An additional band of radiative recombination in the vicinity of 1.22 eV is caused by electron transitions from the conduction band to the deep donor levels Ev+(0.36-0.38) eV, which correspond to the Cr¹⁺ defect entering to clusters. We have also observed the shift of CdTe:Cr absorption edge to the longwave region. This shift is caused by strong lattice deformation near the Cr²⁺ impurity position due to the static Jahn-Teller effect.